Intragenic Deletion in the LIFR Gene in a Long-Term Survivor with Stüve-Wiedemann Syndrome - Hatagami Marques, Júlia (Mol Syndromol, 2015)
Stüve-Wiedemann syndrome (SWS, OMIM 601559) is a rare autosomal recessive bent-bone dysplasia, caused by loss-of-function mutations in the leukemia inhibitory factor receptor (LIFR) gene, which usually leads to early death. Only few patients with long-term survival have been described in the literature. We report on a 5-year-old boy from a consanguineous marriage with molecular analysis for the LIFR gene. Sanger and next-generation sequencing (NGS) of LIFR were performed. Copy number variation analysis with NGS showed a novel mutation as the cause for the syndrome: an intragenic homozygous deletion in LIFR, involving exons 15-20. Bridging PCR was carried out to confirm the intragenic deletion. This is the first description of a large deletion in LIFR, broadening the spectrum of mutations in SWS. Besides the reported allelic heterogeneity, further studies such as exome sequencing are required to identify a novel gene in order to confirm the locus heterogeneity in SWS.